How to perform a percutaneous coronary intervention, when no conventional arterial access site is available: A case report. Issue 6 (November 2022) - Vijayvergiya, Rajesh; Uppal, Lipi; Kasinadhuni, Ganesh; Revaiah, Pruthvi C; Palanivel, Rajan; Lal, Anupam
Coronary artery disease is one of the leading causes of mortality in the world. The presence of concomitant peripheral artery disease increases the risks of cardiovascular events along with limiting the arterial access for coronary intervention. Invasive management of such cases includes either alternate site access or combined peripheral and coronary revascularization. We hereby report a patient of the infrarenal abdominal aorta and bilateral subclavian arterial occlusion, who presented with acute coronary syndrome. To perform the percutaneous coronary intervention, we first performed the endovascular stenting of occluded aortoiliac disease, followed by stenting of the right coronary artery. We had discussed the limitation of arterial access to perform PCI in such a situation.